Benchmarking Community‐Based Couple Therapy: Considering Measurement Reactivity. Issue 4 (8th January 2020) - Quirk, Kelley; Owen, Jesse; Reese, Robert J.; Babins‐Wagner, Robbie; Berzins, Sandy
Abstract : Couple therapy has been shown to be effective in randomized clinical trials; however, results from naturalistic couple therapy have been less consistent. This study utilized a benchmarking approach to compare the effectiveness of couple therapy in a community‐based setting with findings from efficacy treatments, such as treatment within randomized clinical trials . The current study is the largest couple therapy sample published to date ( N =  3, 347 couples). Clients in couple therapy were asked to provide initial and weekly ratings of symptomology on the Outcome Questionnaire (OQ‐45.2) . We found that treatment effect sizes found at community clinics were smaller than efficacy studies (i.e., the benchmark). However, when taking into account measurement reactivity, the effect sizes were comparable . This is the first benchmarking study for community‐based couple therapy, allowing for meaningful comparisons and understanding of outcomes in real‐world couple therapy. Implications for the field are offered in terms of evaluating community‐based psychotherapy studies with benchmarking for couple therapy. Results of this study provide clinicians and researchers a way to meaningfully compare couple therapy outcomes, accounting for differences in community‐based practices and randomized clinical trials. This benchmark also underscores the impact of measurement sensitivity, an issue commonly overlooked in psychotherapy research and practice. Abstract : Se ha demostrado que la terapia de pareja es eficaz en los ensayos clínicos aleatorizados, sin embargo, los resultados de la terapia de pareja naturalista han sido menos consecuentes. Este estudio utilizó un enfoque comparativo para comparar la eficacia de la terapia de pareja en un entorno basado en la comunidad con hallazgos de los tratamientos de eficacia, como los tratamientos dentro de los ensayos clínicos aleatorizados El presente estudio es la muestra más grande de terapia de pareja publicado hasta la fecha ( N = 3347 parejas). Se pidió a los pacientes en terapia de pareja que proporcionen calificaciones iniciales y semanales de la sintomatología en el cuestionario para evaluación de resultados (OQ‐45.2) . Descubrimos que los tamaños del efecto de los tratamientos hallados en las clínicas comunitarias fueron más pequeños que los de los estudios de eficacia (p. ej.: el estudio comparativo). Sin embargo, cuando se tomó en cuenta la reactividad a la medición, los tamaños del efecto fueron comparables. Este es el primer estudio comparativo para la terapia de pareja basada en la comunidad, el cual permite comparaciones significativas y comprensión de los resultados en la terapia de pareja en el mundo real. Se ofrecen las implicancias para el área en cuanto a la evaluación de los estudios de la psicoterapia basada en la comunidad con evaluación comparativa de la terapia de pareja. Los resultados de este estudio proporcionan a los clínicos y a los investigadores una manera de comparar significativamente los resultados de la terapia de pareja, así como de explicar las diferencias en las prácticas basadas en la comunidad y en los ensayos clínicos aleatorizados. Esta evaluación comparativa también subraya el efecto de la sensibilidad a la medición, una cuestión comúnmente pasada por alto en la investigación y la práctica de la psicoterapia. Abstract : 在随机的临床试验中，伴侣疗法的疗效已被证实；然而，实际场景的伴侣疗法之有效性相对而言却没有那么持续稳定。本研究采用一种标杆分析方法来对比基于社区环境中使用伴侣疗法之有效性和随机临床试验中功效疗法的结果。从迄今为止的出版文献来看，本研究使用的伴侣疗法样本数是最多的（N = 3, 347对）。接受伴侣疗法的病人都被要求在结果问卷（OQ‐45.2）上提供初始症状的评定等级和每周的评估等级。我们发现在实际的社区诊所的治疗效应值大小比其功效研究的（即基准水平）要小。但是，如果考虑到测量反应性，效应值则是相当的。这是第一个关于基于社区环境的伴侣疗法的标杆分析研究。本研究进行的是有意义的比较，且增进对现实情境中伴侣疗法之结果的理解。在评估基于社区的心理治疗研究方面以及对伴侣治疗的标杆测试方面均提供了一些启示。这项研究的结果为临床医生和研究人员提供了一种对伴侣治疗结果进行有意义地比较的方法，解释了社区情境下的实际治疗和随机临床试验结果之间的差异。该基准还强调了测量敏感性对结果产生的影响，这种影响在心理治疗研究和实践中通常是被忽略的。